PENGARUH KEDALAMAN AIR TERHADAP HASIL PANEN PADI LAHAN RAWA DI DESA MELAYU ILIR, KABUPATEN BANJAR - Arifin (Fakultas Pertanian UVAYA Banjarmasin, 2025)
This study aims to analyze the relationship between water depth and rice yields in tidal swamps in Melayu Ilir Village, Banjar Regency, South Kalimantan. Data collection was carried out during one planting season with periodic measurements of water depth and rice yields in tons/ha. The analysis was carried out using linear and polynomial regression to determine the best statistical model that represents the relationship between water depth and plant productivity. The results showed that the relationship between water depth and yields was negative and non-linear, with a third-order polynomial model as the best model (R² = 0.995). The optimal water depth to achieve maximum yields is in the range of 10– 20 cm. Increasing water depth above 30 cm tends to cause a significant decrease in yields. This study provides a scientific basis for precise and sustainable irrigation management in swamps.